Level of professionalisme among islamic education trainees in practical teaching - Muhammad, Azhar; Suratman, Azmi Shah; Mustari, Mohd. Ismail; Abdullah, Abdul Hafiz; Jasmi , Kamarul Azmi (Centre for Islamic Studies and Social Development, 2006)
This paper sets out to study the level of professionalism among Islamic Education trainees teachers in practical teaching and also in practical field as a profession in addition. This research carried out to determine the trainees level of professionalism in writing lesson plans, the rules and regulations of the school as well as their mastery in Islamic Education subjects. 58 practical supervisors comprising Centre for Islamic Studies and Social Development (PPIPS) lecturers and cooperative teachers have been selected as the sample. This study used questionnaires to get the information needed and data obtained is evaluated using Likert Scala. It has been found that the level of professionalism among Islamic Education trainees teachers is at a high level during the practical teaching. To conclude, a few problems faced by trainees have been identified and some recommendations are suggested to improve their level of professionalism among Islamic Education trainees teachers at future.